2013
DOI: 10.3389/fpsyg.2013.00983
|View full text |Cite
|
Sign up to set email alerts
|

Lighting direction and visual field modulate perceived intensity of illumination

Abstract: When interpreting object shape from shading the visual system exhibits a strong bias that illumination comes from above and slightly from the left. We asked whether such biases in the perceived direction of illumination might also influence its perceived intensity. Arrays of nine cubes were stereoscopically rendered where individual cubes varied in their 3D pose, but possessed identical triplets of visible faces. Arrays were virtually illuminated from one of four directions: Above-Left, Above-Right, Below-Left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…We did not find significant differences between the PSEs obtained in each location, paired t test, t(14) ¼ 0.525, p ¼ 0.6; the averaged PSEs in log units were Reference Left_visual_field ¼ À0.3039, SD ¼ 0.061, and Reference Right_visual_field ¼ À0.317, SD ¼ 0.047. Interestingly, when the reference stimuli were presented on the right side, the stimuli on the left side were perceived with slightly higher contrast in agreement with McCourt et al (2013) findings; however, in our case this difference was not significant.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We did not find significant differences between the PSEs obtained in each location, paired t test, t(14) ¼ 0.525, p ¼ 0.6; the averaged PSEs in log units were Reference Left_visual_field ¼ À0.3039, SD ¼ 0.061, and Reference Right_visual_field ¼ À0.317, SD ¼ 0.047. Interestingly, when the reference stimuli were presented on the right side, the stimuli on the left side were perceived with slightly higher contrast in agreement with McCourt et al (2013) findings; however, in our case this difference was not significant.…”
Section: Resultssupporting
confidence: 91%
“…Results of conditions 4 and 6 ( Figure 6) show that left-dark and top-dark stimuli were perceived with similar contrast. Previous findings, using 3D cubes presented in a stereo display, have found that arrays of top-dark cubes are perceived more intensely illuminated (higher brightness) than arrays of top-light cubes (McCourt et al, 2013). McCourt et al (2013) suggested that top-dark objects are perceived with higher contrast as a consequence of this increased perceived illumination and also because top-dark stimulus could be interpreted as a convex stimulus illuminated from below.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, under the conditions tested, the spatial location of the gradient checks did not determine the lightness induction effect (but see McCourt et al, 2013 ). We tested two different spatial locations: gradients presented concurrently, in the same row (in the Test and Match checks, Configuration 5), and in parallel, in different rows (in the flankers, Configuration 6).…”
Section: Discussionmentioning
confidence: 97%